2013
DOI: 10.5489/cuaj.850
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term results of pelvic organ prolapse repair using a transvaginal mesh: the experience in Sherbooke, Quebec

Abstract: Objective: The objective was to report our experience on the implantation of the Prolift system since 2005. Methods: Fifty-six patients were operated on between July 2005 and August 2008 by 1 surgeon. The patients were implanted with the transvaginal mesh, the Prolift system, for the treatment of recurrent or high-grade (Baden-Walker stage III or IV) multiple compartment pelvic organ prolapse (POP) associated with symptoms. A concomitant anti-incontinence surgery was performed in 38 patients (68%). Results: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2015
2015
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…Various abdominal and vaginal surgical approaches have been introduced in the past several decades. However, conventional surgical treatments have high recurrence rates of up to 58%, and 20–30% of patients require reoperation for recurrence within 5 years . As a result, a number of synthetic meshes have been designed to reduce recurrence and complication rates in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Various abdominal and vaginal surgical approaches have been introduced in the past several decades. However, conventional surgical treatments have high recurrence rates of up to 58%, and 20–30% of patients require reoperation for recurrence within 5 years . As a result, a number of synthetic meshes have been designed to reduce recurrence and complication rates in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Sanses and colleagues in comparing short-term outcomes of vaginal mesh repair to abdominal sacral colpopexy for management of apical prolapse reported an anatomic cure rate of 98.8% for vaginal mesh repair and 99.3% with abdominal sacral colpopexy at three to six months follow-up [3]. A retrospective study of 56 patients who underwent Prolift ® vaginal mesh procedures reported a cure rate of 91% at 21 months follow-up [11], and another series of 60 patients with median follow-up of 29 months reported success rate of 85% with 15% rate of mesh exposure [6]. Others have reported rates of mesh exposure between 1% and 25% [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…In 11 non-randomized studies (623 patients), nine of which using NAS meshes, no post-surgical infection was detected [33,[36][37][38][39][40][41][42][43][44][45]. Six studies with NAS meshes reported post-surgical hyperthermia, meaning 3.15% out of 755 cases [46][47][48][49][50][51]. Other frequent infections were urinary, low or high (13 studies, 1,899 patients, mean frequency 5.8%), and infection of the surgical site (nine studies, 1,287 patients, mean frequency 2%).…”
Section: Infectionmentioning
confidence: 99%